Implementation of the Mobile Rebo Collaborative Service (LABOLING) at the Population and Civil Registration Service of Indramayu Regency - Meida; Ilham Setiawan; Mulyati Kartini (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Problems in population administration services are still being experienced by residents in Indramayu Regency, especially those living in remote areas who find it difficult to acces service offices. To address thiss challenge, the Department of Population and Civil Registration of Indramayu Regency initiated the Mobile Collaborative Wednesday Service (LABOLING) program as an innovative outreach approach to bring services closer to the community. This study aims to examine the implementation of the LABOLING program, the obstacles encountered, and the strategies used to overcome those obstacles. The research applies Richard Matland’s public policy implementation theory, which consists of four main indicator’s: policy accuracy, implementer accuracy, target accuracy, and environmental accuracy. The research method used is descriptive qualitative, with data collected through interviews, observation, and documentation. The informants in this study include staff from the Departmen of Population and Civil Registratation of Indramayu Regency and community members who received LABOLING services, The results show that the LABOLING program has significantly helped to expand the reach of population administration services. However, several obstacles remain, such as limited insfrastucture, technical issues in the document printing process, and uneven dissemination of the program across all areas. In conclusion, the LABOLING program is a fairly effective public service innovation and can continue to be developed through improvements in its implementations aspects.